Pengembangan Potensi Mangrove sebagai Produk Pangan Fungsional di Kecamatan Wonorejo Surabaya - Ratna Yulistiani; Dedin Finatsiyatull Rosida; Anggita Savitri; Berlianda Meireni Zacharya (Journal of Science and Social Development, 2023)
One of the coastal areas that has large areas of potential mangroves is Wonorejo District, East Surabaya. The Wonorejo Mangrove Ecotourism concept provides economic benefits for people who have creative small industries to improve people's living standards. Pedada fruit (Sonnerita spp) is one of the products of mangrove forests which is rich in nutritional content, rich in antioxidants and dietary fiber which has great potential to be developed as a functional food product. The UPN Veteran East Java community service program in the "UPN Serves" scheme has developed the potential of mangroves (Pedada fruit and Pedada Pulp Flour) into functional food products based on local food. The aim of this community service program is to encourage Wonorejo Mangrove Farmer Group partners to further increase the potential of mangroves as a functional food product to improve the economy and preserve the environment through creative small industries with an appropriate technological approach. The approach method used is in the form of surveys, provision and technical training/guidance, as well as mentoring. The results of the activity show that through knowledge transfer, mentoring and training on appropriate technology, functional food products from pedada fruit and pedada fruit pulp flour have attracted the interest and participation of partners to further utilize the potential of mangroves as functional food products, as well as opening up business opportunities from these activities. The functional products created from this program are Pedada Cookies high in fiber and antioxidants, Pedada Onion Sticks high in fiber, Pedada Fruit Jam high in fiber and vitamin C, and Pedada Jelly Candy high in collagen and vitamin C. The output of this program is Appropriate Technology food products The functional function of mangroves is expected to be a commercial product and superior product of the Wonorejo Surabaya Mangrove Farmers group.